Preparation, Characterization, and Evaluation of Curcumin Cocrystal-Loaded Transdermal Patch. (International Journal of Research in Pharmaceutical Sciences and Technology, 2026)
Curcumin, a naturally occurring polyphenolic compound derived from turmeric, possesses significant anti-inflammatory, antioxidant, and anticancer properties. However, its therapeutic application is limited by poor aqueous solubility and low bioavailability. The present study aimed to prepare curcumin cocrystals to enhance its physicochemical properties and incorporate them into transdermal patches for sustained drug delivery. Curcumin cocrystals were prepared and characterized using Fourier Transform Infrared Spectroscopy (FTIR), Differential Scanning Calorimetry (DSC), and X-ray Diffraction (XRD) to confirm cocrystal formation and evaluate solid-state characteristics. The cocrystals were then formulated into transdermal patches using suitable polymers and evaluated for physicochemical properties, including thickness, weight variation, folding endurance, moisture content, moisture uptake, surface pH, drug content, and in vitro drug release. Five formulations (A1–A5) were developed and compared based on their performance. Among them, formulation A3 demonstrated superior physicochemical characteristics and exhibited the highest cumulative drug release compared with the other formulations. The findings indicate that cocrystallization combined with transdermal drug delivery significantly improves the performance of curcumin and offers a promising strategy for enhancing its therapeutic potential.
Keywords: Curcumin; Cocrystal; Transdermal Patch; Analytical Characterization; Bioavailability